2010
DOI: 10.1124/dmd.109.031047
|View full text |Cite
|
Sign up to set email alerts
|

Phase II Metabolism of Hesperetin by Individual UDP-Glucuronosyltransferases and Sulfotransferases and Rat and Human Tissue Samples

Abstract: ABSTRACT:Phase II metabolism by UDP-glucuronosyltransferases (UGTs) and sulfotransferases (SULTs) is the predominant metabolic pathway during the first-pass metabolism of hesperetin (4-methoxy-3,5,7-trihydroxyflavanone). In the present study, we have determined the kinetics for glucuronidation and sulfonation of hesperetin by 12 individual UGT and 12 individual SULT enzymes as well as by human or rat small intestinal, colonic, and hepatic microsomal and cytosolic fractions. Results demonstrate that hesperetin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
64
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 90 publications
(73 citation statements)
references
References 39 publications
8
64
1
Order By: Relevance
“…For example, human recombinant UGT1A1 catalyzed mainly the 3Ј-hydroxyl quercetin glucuronidation, whereas UGT1A6 preferentially catalyzed the 4Ј-and 7-hydroxyl moieties (Boersma et al, 2002). In addition, such regioselectivity of UGT isoforms is dependent on flavonoid subfamilies, e.g., human recombinant UGT1A1 mainly catalyzed the 7-hydroxyl position of the flavanone hesperetin and UGT1A7 selectively glucuronidated the 3Ј-hydroxyl position (Brand et al, 2010). Furthermore, the regioselectivity of flavonoid glucuronidation in intestine is species-dependent, with 7% quercetin conjugated at the 7-hydroxy moiety in humans and 41% at this position in rats (Boersma et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, human recombinant UGT1A1 catalyzed mainly the 3Ј-hydroxyl quercetin glucuronidation, whereas UGT1A6 preferentially catalyzed the 4Ј-and 7-hydroxyl moieties (Boersma et al, 2002). In addition, such regioselectivity of UGT isoforms is dependent on flavonoid subfamilies, e.g., human recombinant UGT1A1 mainly catalyzed the 7-hydroxyl position of the flavanone hesperetin and UGT1A7 selectively glucuronidated the 3Ј-hydroxyl position (Brand et al, 2010). Furthermore, the regioselectivity of flavonoid glucuronidation in intestine is species-dependent, with 7% quercetin conjugated at the 7-hydroxy moiety in humans and 41% at this position in rats (Boersma et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…UGT1A1 and UGT1A7 were positively correlated to rates of SI quercetin glucuronidation, particularly when stratified with age. Of interest, Brand et al (2010) concluded that UGT1A1 and UGT1A7 were the FIG. 7.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with the critical roles of glucuronidation and sulfonation in the first-pass clearance of hesperetin, an array of UDP-glucuronosyltransferase (UGT) enzymes (i.e., UGT1A1, UGT1A3, UGT1A6, UGT1A7, UGT1A8, UGT1A9, UGT1A10, UGT2B4, UGT2B7, and UGT2B15) and multiple sulfotransferase (SULT) enzymes (including SULT1A1, SULT1A3, and SULT2A1) are actively involved in conjugating hesperetin (Brand et al, 2010a). In addition, hesperetin conjugates are found to be the main circulating metabolites in humans and rodents, confirming the importance of conjugative metabolism in hesperetin disposition (Matsumoto et al, 2004;Takumi et al, 2012;Yamamoto et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Hesperetin is extensively metabolized by phase II enzymes to form sulfate and glucuronide conjugates, resulting in exceedingly low bioavailability after oral administration (Brand et al, 2008(Brand et al, , 2010. Recent studies have indicated that phase II conjugates of hesperetin retain the biologic activities of the parent molecule (Takumi et al, 2012;Yang et al, 2012).…”
Section: Introductionmentioning
confidence: 99%